The use of Oil Shale for Road Coating (Global Journals of Research in Engineering, 2023)
The world s strong economic growth and increasing populations have generated a remarkably growing demand for resources especially energy Current conventional sources cannot meet the future needs Efforts are being focused on renewable energies deep-sea oil and the development of new techniques to value heavy oils tar sands and oil shale This could bridge the gap between energy demand and supply Several countries with oil shale deposits have launched projects to examine the possibility of exploiting these deposits Morocco is one of these countries with significant oil shale deposits in the Middle Atlas Timahdit Tarfaya Tangier and Grand Atlas regions Fig 1 1